satisfaction of the janbazan ( veteran ) from complemented insurance services and their connection with type and percentage of injury - S. Hosseini farhangi; F. Dortaj; M. Talebi; F. Ghaemi (Afarand Scholarly Publishing Institute, 2009)
Purpose : Aim from this research was satisfaction of the Janbazan (veterans) from complemented insurance services.   Methods and Materials : For this cause examined satisfaction of the Janbazan (veterans) from complemented insurance services and their connection with type and percentage of injury and other connection factor. For answer to these objectives were selected 400 janbaz in Tehran with stratified sampling and data were collected with questionnaire of 32 segments, that designed in this field. Also dat analyzed with descriptive statistic, on - anova , Spearman and Pearson correlation and chi - square test .   Results : satisfaction of the janbazan from complemented insurance services is mean. Between satisfaction from services health that presenting to segregation of type of injury view few different that this difference isn't significant but in satisfaction of janbazan from services health to segregation of percentage of injury, view most different .